Peningkatan Pemahaman Konsep Matematika Pada Pokok Bahasan Segiempat Dan Segitiga Melalui Metode Problem Based Learning (PTK pada Siswa Kelas VII Semester Genap SMP Negeri 1 Grobogan Tahun Ajaran 2015/2016) - Pratiwi, Hana Dewi, Idris Harta, MA, Ph. D (2016)
This research aims to improve understanding of mathematical concepts on the subject of rectangles and triangles through Problem Based Learning method. This research is a classroom action research. The subject of this research are students and teacher of class VII 7 SMP Negeri 1 Grobogan. Implementation of class actions performed during the four cycles of four meetings. The techniques of collecting data was observation , documentation , test methods and field notes. To ensure the validity of data used triangulation of sources and techniques. Data analysis techniques used are data reduction , data presentation and verification of data. The results showed an increased understanding of mathematical concepts on the subject of rectangles and triangles through Problem Based Learning method seen from the percentage of: ( 1 ) students who are able to restate the purpose of the lesson was learned , before action 10 students ( 25.00%), after the act became 28 students ( 70.00 % ); ( 2 ) students who are able to solve problems correctly in accordance with the steps right , prior to the action 14 students ( 35.00 % ), after the act became 33 students ( 82.50 % ); ( 3 ) students who are able to use a concept for solving the problem , before the act of 11 students ( 27.50 % ), after the act became 30 students ( 75.00 % ). It can be concluded that the learning methods Problem Based Learning can enhance students' understanding of mathematical concepts.